DEVELOPMENT OF CURRICULUM AND METHODOLOGY OF SPECIAL SUBJECTS - Urinov Uygun Abdullayevich; Urakova Habiba Bakhtiyorovna (Journals Park Publishing, 2023)
This in the article special of sciences educational and methodological supply work exit about word goes. Examples of the main parts of educational-methodological complexes in specialized subjects given. Expertise sciences teaching to improve the quality, teaching tools included in the teaching-methodological complex are explained in detail.
Keywords: lesson, student, new pedagogical technology, educational system, science, method, knowledge, skills, competence, interest.